ANALYSIS OF CHILDREN'S WINTER OUTERWEAR PRODUCTION REQUIREMENTS (Multidisciplinary Journal of Science and Technology, 2025)
This article explores the critical aspects of selecting and applying technological processes in the production of winter outerwear for children. Such garments must effectively protect children from cold and damp environmental conditions, retain body heat, and ensure freedom of movement. To fully meet these functional requirements, the use of modern materials—such as synthetic insulation (e.g., sintepon, hollofan) and membrane-coated fabrics—as well as advanced sewing technologies is essential. The study analyzes the main stages of the production process, including material selection, garment design and construction, sewing techniques, and final finishing procedures. Moreover, the article scientifically examines the relationship between technological choices and product quality, durability, and ergonomic performance. The findings are presented in the form of practical recommendations for manufacturers specializing in children's clothing.